EFEKTIVITAS MANAJEMEN PENJUALAN PAKET UMRAH DALAM MENINGKATKAN PELAYANAN TRAVEL HAJI DAN UMRAH PERSFEKTIF EKONOMI ISLAM - Agus Ahmad Faruk; Hasan Basri; Mei Amimah (ARMUZNA : Jurnal Manajemen Haji dan Umrah (MHU), 2024)
This research is motivated by lookingn at the reality of the management of sales of Umrah packages in Tasikmalaya City, which seems to have not been optimally managed to improve services for Umrah travel businesses in the community. In fact, if you look at daily activities, congregational services are carried out every day. Community pilgrim services managed by Umrah Travel and KBIHU show that the realization figures each year fluctuate and have not reached the target. The aim of this research is to determine the effectiveness of public pilgrim service management carried out by Umrah Travel and KBIHU in improving services to the community's Umrah travel business with an Islamic economic perspective. This research uses qualitative field research methods, namely research that studies phenomena in their natural environment. The techniques used are observation, interviews and documentation. Research Results: The effectiveness of community service management in improving services for the Umrah travel business in Indihiang Community is generally not optimal. Based on the service indicator criteria, physical evidence, reliability, responsiveness and empathy are not yet optimal, while only the guarantee aspect is optimal. As for the Islamic economic review of the effectiveness of community congregation service management in improving services for the community's Umrah travel business in the Indihiang community, only a few have been implemented. Islamic economic principles, namely the principles of monotheism and brotherhood, the principles of work and productivity.